Infectious Etiologies of Myelopathy - Ho, Emily L. (Seminars in Neurology, 2012)
Myelopathy refers to a spinal cord disorder that presents with motor and/or sensory deficits. Infectious agents that cause myelopathy do so by either direct infection of neural structures (e.g., polio), a parainfectious mechanism (with a presumed autoimmune pathogenesis), or as a result of involvement of structures adjoining the spinal cord, which may cause a compressive myelopathy. This review of infectious causes of myelopathy focuses on pathogens that are most relevant to clinicians in North America.
Keywords: myelopathy; infectious disease; spinal cord; bacteria; virus